ANALISIS LINGKUNGAN KERJA DAN KETERLIBATAN PEGAWAI TERHADAP KINERJA PEGAWAI DI SATUAN POLISI PAMONG PRAJA (SATPOL PP) KABUPATEN LAHAT - Della, Triska; Rismansyah, Rismansyah; Mafra, Nisa Ulul’ (Universitas Nusa Cendana, 2024)
The purpose of this study was to find out the influence of the Work Environment and Employee Involvement on Employee Performance in the Civil Service Police Unit (Satpol PP) in Lahat Regency. The sampling method in this study used a purposive sampling method, which is the technique of determining the sample with consideration of certain criteria. The sample in this study was taken based on the number of Civil Servants (PNS) in the Civil Service Police Unit and the Lahat Regency Damkar, totaling 52 people. The data collection method used is questionnaires. The data analysis technique used in this study was Multiple Linear Regression, Correlation Analysis, Determination Analysis, hypothesis t-test, and hypothesis F-test with the help of SPSS 22 for Windows. The results of the study show that there is a significant influence partially and simultaneously between the Work Environment and Employee Involvement on Employee Performance in the Civil Service Police Unit (Satpol PP) of Lahat Regency. Keywords: Work Environment; Employee Engagement; Employee Performance